Addiction to Online Games Affects The Attention Levels Of Medical Students Of Pelita Harapan University - Johanes David Hendrijanto; Claudia Kinsky Irawan1 Irawan; Vivien Puspitasari (Lumina : Indonesian Journal of Neurology, 2025)
Background: Epidemiologically, the incidence of online games addiction in students in Indonesia in 2013 is estimated to be around 10.15%. Addiction to online games is one of the factors that might affect a person’s level of attention. Previous studies had shown that there are positive and negative effects of attention function. There are also several studies that have reviewed the relationship between online games addiction and cognitive function but only a few studies focus on the level of attention. The study was conducted to determine the relationship of online games addiction with the level of attention to students. Methods: This study uses a cross-sectional method. A sample of 158 peoples, who are students of the Faculty of Medicine at the University of Pelita Harapan in 2017 and were selected using a purposive technique. Data was collected from February to March 2020. The results were processed with Chi Square using SPSS version 25.0 software. Results: Of the 158 samples needed, only 97 samples were collected due to COVID-19 and power by 56%. Of the 93 samples that met the inclusion criteria, 22.6% were addicted to games. In the game’s addiction group, it was found that 23.8% experienced a decrease in forward attention and 57.1% experienced a decrease in backward attention. (forward: p value = 0,000, backward: p value = 0,001). Conclusion: In conclusion, a significant relationship was found between online game addiction and decreased attention levels.